Molecular identification and population genetic study of Elaeidobius kamerunicus Faust. (Coleoptera: Curculionidae) from Indonesia, Malaysia and Cameroon based on mitochondrial gene - Van Basten Tambunan; Ardha Apriyanto; Walter Ajambang; Culbertson Enow Etta; Bandung Sahari; Damayanti Buchori; Purnama Hidayat (Society for Indonesian Biodiversity, 2020)
Abstract. Tambunan VB, Apriyanto A, Ajambang W, Etta CE, Sahari B, Buchori D, Hidayat P. 2020. Molecular identification and population genetic study of Elaeidobius kamerunicus Faust. (Coleoptera: Curculionidae) from Indonesia, Malaysia and Cameroon based on mitochondrial gene. Biodiversitas 21: 3263-3270. Oil palm pollinating weevil Elaeidobius kamerunicus is a very important insect pollinator in oil palm plantation. However, there is still lack of information about molecular identification and population genetic study in this species. The purpose of this study was to explore the effectiveness of oil palm pollinating weevil identification using mitochondrial DNA of COI gene and to assess its genetic variation between different locations and countries. We sequenced the DNA barcode of 36 individuals of this species using the mtDNA Cytochrome Oxidase I (COI) gene to explore their genetic variation, identity and phylogenetic relationship. The COI gene sequences generated from this study were successful in identifying E. kamerunicus. Phylogenetic analysis also revealed 3 well-supported monophyletic haplogroups of E. kamerunicus population. In addition, genetic differentiation analysis revealed that most populations from Indonesia were different from Malaysian and Cameroonian populations indicating that there was a genetic variation between the population samples from these countries. The overall E. kamerunicus used in this study were geographically structured in two regions; outside Indonesia region (Cameroon and Malaysia) and Indonesia region. These results demonstrate the feasibility of using COI gene sequence for molecular identification and population genetic study of E. kamerunicus species.